Takhrij and Syarah Hadith of Chemistry: Legal Studies on the Use of Alcohol as a Solvent (Solvent) in Cough Medicine - Nabil Fasha Inaya; Arif Maulana; Tina Dewi Rosahdi; Eni Zulaiha; Busro Busro (Gunung Djati Conference Series, 2021)
The purpose of this research is to discuss the hadith of the Prophet. about the law of using alcohol as a solvent (solvent) in cough medicines. This research method is qualitative through the takhrij and sharah hadith approaches with chemical analysis. The results and discussion of this study, although in fact alcohol is the main content of khamar so that the drink can cause the consumer to become drunk, alcohol when separated from the khamar is a different matter because of the different composition of particles and the way of making it. In terms of the hadith of the Prophet Muhammad, alcohol contained in cough medicine is permissible (mubah), because basically the Prophet's hadith regarding forbidden khamar is in the context of drinks that already contain an intoxicating element, so if you drink it in small amounts or in large quantities the law is haram. Meanwhile, in terms of its use as a solvent in cough medicines it is not the case if the levels remain within the predetermined limits, namely not more than 1%. The conclusion of this research is takhrij and syarah hadith of the Prophet. It is hoped that it will become a reference for Muslims to be more careful in consuming cough medicine, which is indicated to contain alcohol compounds whose levels reach more than one percent of its content. This study recommends related agencies to tighten supervision of halal labeling on medicinal products, so that people are not fooled into consuming products that can endanger public health.